Soft Skill Development Strengthening Program Business Entrepreneurship - Nugroho Juli Setiadi; Agung Hari Sasongko; Jajat Sudrajat; Meiryani Meiryani (Bina Nusantara University, 2021)
The program to strengthen the concept of genetic intelligence as a concept to improve student soft skills was chosen as one of the concepts and methods to be used for student entrepreneurial development using the experiential learning model. Experiential learning approach is a learning approach where knowledge is constructed through experience transformation. In the concept of genetic intelligence or familiar with the term STIFIn Concept, there are 5 parts of the brain, namely Sensing, Thinking, Intuiting, Feeling and Instinct. The brain turns out to have different parts and chemistry. The results of the STIFIn Concept analysis are knowing the dominance of a person's right or left brain, so that it can be the basis for choosing the right field of entrepreneurship, business partners and business mentors according to their genetic intelligence.